Unraveling complexity in changing mental health care towards person-centered care - Lorenz-Artz, Karin; Bierbooms, Joyce; Bongers, Inge (Frontiers in Psychiatry, 2023)
Background Mental health care (MHC) needs to shift towards person-centered care to better meet people’s individual needs. Open Dialogue (OD) is well-aligned with this perspective and brings it into practice. This study focuses on exploring the change process within a pilot project involving three MHC teams as they transition to a person-centered OD practice. Our aim is to identify and reflect on the challenges faced by MHC professionals in adopting person-centered care, and shedding light on the underlying complexity of these challenges. By gaining a better understanding of these obstacles, we hope to contribute to the adoption of the person-centered approach in MHC practice. Methods Our research employed a qualitative design, involving a total of 14 semi-structured interviews with MHC professionals who were either trained in OD, OD trainees, or MHC professionals without OD training. To analyze the data, we utilized a hybrid approach that combined deductive – and inductive thematic analysis. Results We identified four distinctive challenges: (1) understanding and knowledge transfer, (2) (inter)personal process, (3) emotional discomfort, and (4) the need for multi-stakeholder participation and support. In practice, these challenges intersect and the appearance of and relationships between these challenges are not linear or disentangleable. Conclusion Upon careful consideration of these interdependent challenges, it became evident that embedding a person-centered approach like OD brings about systemic change, leading to an unfamiliar situation X. The research findings indicated that understanding and conveying the concept of person-centered care in practical settings poses significant challenges. The field of knowledge management helps to capture the complexity of understanding and transferring this knowledge. The change process necessitates an (inter)personal process and elicits emotional discomfort, as person-centered OD practice confronts a deeply entrenched paradigm in MHC. Achieving a shared understanding of person-centered care requires dedicated time and attention, while introducing this approach prompts broader discussions on underlying values and human rights in MHC. Current implementation efforts may underestimate or overlook these underlying values, but initiating an open dialogue can serve as an initial step in addressing the complexities.